2018
DOI: 10.3168/jds.2018-14680
|View full text |Cite
|
Sign up to set email alerts
|

Canadian National Dairy Study: Heifer calf management

Abstract: In the past decade, substantial changes have occurred in the way dairy heifer calves are managed. The objectives of this study, part of phase I of the 2015 Canadian National Dairy Study, were to examine heifer calf health and adoption of rearing practices, and to explore factors associated with different rearing strategies on Canadian dairy farms. The questionnaire was open to all licensed dairy producers in Canada and had a 12% response rate (n = 1,373). Fifty-one percent of respondents reported never allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…Our results for dairy farms showed 73% did not rely solely on natural suckling to ensure the calf got enough colostrum. This was in-line with a survey of Canadian dairy farmers, where it was found 82% of farmers implemented management practices to ensure the calf got colostrum in the first hours of life (Winder et al, 2018). However, there is still progress to be made in this area, as 46% of calves received 3 litres or less in the first 24 hours, which is well below AHDB recommendations of 6 litres in the first 12 hours.…”
Section: Discussionsupporting
confidence: 74%
“…Our results for dairy farms showed 73% did not rely solely on natural suckling to ensure the calf got enough colostrum. This was in-line with a survey of Canadian dairy farmers, where it was found 82% of farmers implemented management practices to ensure the calf got colostrum in the first hours of life (Winder et al, 2018). However, there is still progress to be made in this area, as 46% of calves received 3 litres or less in the first 24 hours, which is well below AHDB recommendations of 6 litres in the first 12 hours.…”
Section: Discussionsupporting
confidence: 74%
“…An additional 6% of dairy heifers die during the preweaning period (USDA, 2018). A Canadian study by Winder et al (2018) reported a stillbirth rate of 4.9% and preweaning mortality of 6.4%, similar to values reported for the United States.…”
supporting
confidence: 76%
“…Frequent early measurements of serum IgG, as done within this study and others (Desjardins-Morrissette et al, 2018;Fischer et al, 2018), can improve our understanding of gastrointestinal IgG permeation kinetics to determine what drives between-calf variation. This may help us understand why calves often fail to achieve adequate PT (12.1 and 26.7% of calves with serum IgG <10 and 15 g/L, respectively; Shivley et al, 2018) when 67% of producers report following recommended colostrumfeeding practices (Winder et al, 2018) and 14.2% of FPT continues to occur in calves with no risk factors (Shivley et al, 2018). In particular, deducing why calf responses to colostrum feedings are so variable is critical to ensuring calf welfare and benchmarking should FPT thresholds be increased to serum IgG >15 g/L (Furman-Fratczak et al, 2011) or 20 g/L (Chigerwe et al, 2015) in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 12.1 to 19.2% of calves fail passive transfer (PT; Beam et al, 2009;Shivley et al, 2018) at the commonly used threshold (serum IgG <10 g/L), and we can expect on-farm FPT rates to concurrently rise with an increased FPT threshold, as evidenced by 26.7% of calves having serum IgG <15 g/L (Shivley et al, 2018). This presents an opportunity for the dairy industry to improve newborn calf management practices on-farm and reduce the excessive dairy calf morbidity (33.9%; Urie et al, 2018) and mortality (5.0 to 6.4%; Urie et al, 2018;Winder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%